WOMEN-WRITERS IN ENGLISH LITERATURE - Yuldasheva Mahinur Baxodir qizi; Khamitov Eldorbek Erkin o'g'li (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: Women writers have made significant contributions to English literature throughout history, despite facing barriers and challenges due to their gender. This article explores the evolution and impact of women writers in English literature, from the early pioneers to contemporary voices. By examining the works of key female authors and their portrayal of gender, identity, and societal norms, this article sheds light on the unique perspectives and narratives that women bring to the literary world.